Ethnomathematics-based guided discovery learning using Gedung Sate to enhance junior high school students’ mathematical connection ability - Virliani, Viera; Wahyudin, Wahyudin; Priatna, Nanang; Turmudi, Turmudi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Junior high school pupils still have relatively low mathematical connection abilities, despite this being one of the key process requirements in mathematics learning. Through guided discovery and cultural contexts, the ethnomathematics method and the Guided Discovery Learning (GDL) model have the potential to foster significant conceptual understanding. This study aims to assess the extent to which ethnomathematics-based GDL training at Gedung Sate improves junior high school students' mathematical connection skills. The study used a quantitative, pre-experimental one-group pretest–posttest design. The research participants were 12 ninth-graders from Darul Mukhlisin Junior High School in West Bandung Regency, West Java. The instrument was a reliable and valid descriptive evaluation of mathematical connection skills. The data were analyzed using the Shapiro-Wilk normality test, the homogeneity test, the paired samples t-test, and N-gain. The average score rose from 25.68 to 68.74 with a significant difference (p < 0.001), according to the data. At 0.554, the average N-gain value fell into the moderate range. While linkages between mathematical concepts remained low (0.12), the indicators of mathematical connections with other disciplines (0.83) and real life (0.80) saw the largest increases. Based on the research findings, the Gedung Sate ethnomathematics-based GDL has implications as an effective strategy for strengthening students' mathematical connections in context.